The The Case of Two Year 5’s Understanding of Fractions Addition: An Insight into Their Strategies - Masitah Shahrill; Ratu Ilma Indra Putri; Nor’Arifahwati Abbas (Mathematics Education Journal, 2026)
The level of pupils’ accuracy in elaborating their strategies provides important insight into their understanding of fractions addition. This study had a dual purpose: to explore the strategies used by Year 5 pupils when computing fractions addition involving like fractions (FAWL), unlike fractions with related multiples (FARM), and unlike fractions without related multiples (FAWORM), and to examine the mathematical accuracy of their explanations. A qualitative case study design was employed, involving two Year 5 pupils from two primary schools in Brunei who participated in five interview sessions. Data were collected through task-based activities and stimulated recall interviews. The findings revealed a limited range of strategies across the three task types and two contrasting levels of accuracy in pupils’ explanations, despite both pupils arriving at correct answers for all fractions addition tasks. While some explanations reflected procedural descriptions, others demonstrated an accurate understanding through explicit reference to key concepts such as ‘same size’ and ‘same value’. These findings reinforce the view that correct answers alone do not guarantee conceptual understanding and highlight the importance of examining pupils’ verbal elaborations alongside their written strategies when interpreting their understanding of fractions addition.